2004
DOI: 10.1128/jb.186.13.4246-4253.2004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Streptococcus gordonii Beta-Glucoside Metabolism Systems in Adhesion, Biofilm Formation, and In Vivo Gene Expression

Abstract: Streptococcus gordonii genes involved in beta-glucoside metabolism are induced in vivo on infected heart valves during experimental endocarditis and in vitro during biofilm formation on saliva-coated hydroxyapatite (sHA). To determine the roles of beta-glucoside metabolism systems in biofilm formation, the loci of these induced genes were analyzed. To confirm the function of genes in each locus, strains were constructed with gene inactivation, deletion, and/or reporter gene fusions. Four novel systems responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 45 publications
3
74
0
Order By: Relevance
“…two-component regulatory system (15). A previous study has shown that catabolite control protein A (CcpA) functions in carbon catabolite repression of lactose-inducible ␤-galactosidase activity in S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…two-component regulatory system (15). A previous study has shown that catabolite control protein A (CcpA) functions in carbon catabolite repression of lactose-inducible ␤-galactosidase activity in S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Closely related proteins, however, were represented by the deduced products of the bfp locus in the S. gordonii strain Challis NCTC 7688 (www.tigr.org) (Lin Tao, personal communication), which is involved in biofilm formation (data not shown) (15).…”
Section: Vol 189 2007 the Two-component System Tcs08 In S Pneumonimentioning
confidence: 99%
“…Thus, mutations in genes encoding components of quorumsensing systems, e.g., comCDE (354); TCSS, e.g., vicRK (543); GBPs (370); and metal ion permeases (503) can impair S. mutans biofilm formation. Optimal biofilm formation by S. gordonii and S. sanguinis also requires multiple gene products including sortase (428) and proteins involved with ␤-glucoside metabolism and carbon catabolite control (296,364), nucleotide biosynthesis (181), oxidative stress (322,363), and environmental sensing and signaling (193). The growth of nonmitis-group streptococci as biofilms is only just beginning to be studied, but the complexities of M serotypes, capsular serotypes, and the expression of pilus types and antigenically variable surface proteins will probably make interpretations of the molecular pathways involved extremely difficult.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…We found that high-risk strains (HR group) were significantly less able than low-risk strains (LR group) to use ␣-Dglucose-1-phosphate, D-ribose, ␤-methyl-D-glucoside, and D,L-␣-glycerol phosphate, and none of the 95 substrates were better used by the HR group than by the LR group (Table 1). The adaptation of a pathogen's metabolism to its environment can provide it with an advantage for growth, survival, and virulence (2,6,11,21). The loss of catabolic function by S. agalactiae strains observed here may be the result of genetic processes that have improved the organism's adaptation to conditions that generate neonatal meningitis.…”
Section: Discussionmentioning
confidence: 83%